CONSTRUCTING INDIGENOUS ACCOUNTING STANDARDS IN BALI: A STUDY OF IDENTITY POLITICS - Atmadja, Anantawikrama Tungga; Karyada, I Putu Fery; Adiputra, Made Pradana; Werastuti, Desak Nyoman Sri (Proceeding of TEAMS: The International Conference on Tourism, Economic, Accounting, Management and Social Science, 2025)
This paper examines the formation of indigenous accounting standards in Bali as a manifestation of identity politics within the accounting discipline. It highlights how accounting practices, often considered neutral and technical, are deeply embedded in ideological and political structures reflecting dominant values. The central issue addressed in this study is: How can identity politics be reflected in accounting practice and the preparation of customary accounting standards as a manifestation of identity politics in Bali? The novelty of this study lies in its use of a critical accounting approach integrated with identity politics theory to analyse the process of standard setting within indigenous contexts. While previous studies have highlighted indigenous accounting as a form of resistance to colonial systems, few have explored the institutionalisation of these practices through formal policy, particularly in the Indonesian context. The research method is a critical literature review that synthesises postcolonial, critical accounting, and cultural identity frameworks. It draws from secondary sources, government regulations, and theoretical discourses to reveal the symbolic and political dimensions behind developing indigenous accounting standards in Bali. The findings indicate that formulating Indigenous accounting standards in Bali is not merely an administrative innovation but a cultural-political project that asserts local identity, challenges the universality of conventional accounting systems, and opens epistemological space for indigenous representation. However, it also risks being co-opted by formal power structures, thus requiring participatory safeguards to preserve authenticity. This study concludes that the initiative to develop indigenous accounting standards must be understood as part of a broader decolonial project that emphasises context-sensitive accountability and challenges epistemic marginalisation. It contributes to the discourse on alternative accounting by advocating for systems that are not only technically sound but also culturally resonant and socially just.